Chemical composition of matrix-embedded ternary II–VI nanocrystals derived from first- and second-order Raman spectra. (December 2016) - Azhniuk, Yu.M.; Hutych, Yu.I.; Lopushansky, V.V.; Prymak, M.V.; Gomonnai, A.V.; Zahn, D.R.T.
Abstract: A one- and multiphonon Raman scattering study is performed for an extensive set of CdS1– x Se x, Cd1– y Zn y S, Cd1– y Zn y Se, and CdSe1– x Te x nanocrystals to investigate the applicability of first- and second-order Raman spectra for the determination of the matrix-embedded ternary nanocrystal composition. For one-mode ternary systems both the LO and 2LO phonon frequencies in the Raman spectra are shown to be a good measure of the nanocrystal composition. For two-mode systems, the approaches based on the difference of the LO phonon frequencies (first-order Raman spectra) or double LO overtone and combination tone frequencies (second-order Raman spectra) as well as on the LO phonon band intensity ratios are analysed. The weak electron–phonon coupling in the II–VI nanocrystals and the polaron constant values for the nanocrystal sublattices are discussed. Highlights: Raman scattering study for several II–VI ternary nanocrystal systems is performed. For one-mode systems LO and 2LO phonon frequencies are a good measure of composition. For two-mode systems, phonon frequency differences and intensity ratios are analysed.